Distribution of antibodies against Neospora caninum, BVDV and BHV-1 among cows in brazilian dairy herds with reproductive disorders. - Mineo, Tiago W P; Alenius, Stefan; Näslund, Katarina; Montassier, Hélio J; Björkman, Camilla (My University, 2006)
Neospora caninum, bovine viral diarrhea virus (BVDV) and bovine herpes virus 1 (BHV-1) are worldwide spread pathogens associated with reproductive problems in cattle. The present work aimed to observe the infection pattern of these three pathogens in two dairy herds with distinct reproductive managements from Triângulo Mineiro, Minas Gerais State, Brazil. The herds were not vaccinated against either N. caninum, BVDV or BHV-1. Blood samples were collected and analyzed for presence of specific antibodies, and N. caninum IgG avidity was measured in N. caninum positive samples. In herd 1, 34 out of 174 sampled cows (20%) had antibodies to N. caninum and the seropositivity of BVDV and BHV-1 were 62% and 86%, respectively. Of 69 sampled cows in herd 2. 7 (10%) had antibodies to N. caninum, and 49% and 39% were seropositive to BVDV and BHV-1, respectively. The IgG avidity profiles indicated that N. caninum had been present in both herds for some years and that herd 1 had an ongoing horizontal spread of the parasite. The results indicate that the studied reproductive pathogens were present in the herds and partly may have contributed to their reproductive problems.
Keywords: protozoon antibody; virus antibody; animal; blood; Bovine diarrhea virus; Brazil; cattle; cattle disease; dairying; epidemiology; female; immunology; Infectious bovine rhinotracheitis virus; Neospora; reproduction; Animals; Antibodies, Protozoan; Antibodies, Viral; Cattle; Cattle Diseases; Dairying; Diarrhea Viruses, Bovine Viral; Female; Herpesvirus 1, Bovine; Reproduction; Seroepidemiologic Studies